2019
DOI: 10.1002/pmic.201800165
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Regulating Microvesicle Biogenesis and Multidrug Resistance in Cancer

Abstract: Microvesicles (MV) are emerging as important mediators of intercellular communication. While MVs are important signaling vectors for many physiological processes, they are also implicated in cancer pathology and progression. Cellular activation is perhaps the most widely reported initiator of MV biogenesis, however, the precise mechanism remains undefined. Uncovering the proteins involved in regulating MV biogenesis is of interest given their role in the dissemination of deleterious cancer traits. MVs shed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 231 publications
(281 reference statements)
0
39
0
Order By: Relevance
“…Increased PS has been correlated with tumour aggressivity 36 and its presence on MPs has been shown to be associated with neovascularization through interactions with vascular endothelial cells 37 . PS is also an MP marker, its presence arising from the loss of phospholipid asymmetry during MP biogenesis 18 . PS + MP counts hence also coincide with increased tumour burden.…”
Section: An Increase In Ps + Mps Is Associated With Progressive Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Increased PS has been correlated with tumour aggressivity 36 and its presence on MPs has been shown to be associated with neovascularization through interactions with vascular endothelial cells 37 . PS is also an MP marker, its presence arising from the loss of phospholipid asymmetry during MP biogenesis 18 . PS + MP counts hence also coincide with increased tumour burden.…”
Section: An Increase In Ps + Mps Is Associated With Progressive Diseasementioning
confidence: 99%
“…Microparticles (MPs) are a subset of extracellular vesicles (0.1−1 µm in diameter) released from the plasma membranes of most cell types 15 . MPs differ from other extracellular vesicles by virtue of their size, biogenesis and cargo [16][17][18] . Circulating MPs have been detected systemically for many cancers including MM, breast, prostate, and lung cancer [19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…This report added another dimension to the ways that cells can acquire a particular cell surface protein-mediated phenotype, such as multidrug resistance [ 100 ]. Since then, numerous studies have confirmed the finding of Levchenko et al [ 108 ], showing that intercellular Pgp transfer occurs in different cancer cell lines, and exploring mechanisms involved in this transfer [ 69 , 109 , 110 , 111 , 112 ].…”
Section: Regulation Of Pgp At the Bbb: Novel Mechanismsmentioning
confidence: 76%
“…At present, the major therapeutic methods of cancer include surgery, chemotherapy, radiotherapy, and immunotherapy . Resistance to treatment with anticancer agents remains a major clinical problem, resulting in anticancer treatment failure . The problem of chemoresistance is complex, mainly because several factors are involved, such as overexpression of drug efflux pumps, drug inactivation, DNA repair mechanisms, and alterations or mutations in the drug target .…”
Section: Introductionmentioning
confidence: 99%
“…2 Resistance to treatment with anticancer agents remains a major clinical problem, resulting in anticancer treatment failure. 3 The problem of chemoresistance is complex, mainly because several factors are involved, such as overexpression of drug efflux pumps, drug inactivation, DNA repair mechanisms, and alterations or mutations in the drug target. 4 Radioresistance is caused by a variety of factors that include the intrinsic biology that arises from the aberrant genetic makeup of tumor cells, the extensive heterogeneity of brain tumors, and the tumor microenvironment, which fosters and supports conditions that limit the response to radiation.…”
Section: Introductionmentioning
confidence: 99%